Penerapan Metode Tartili dalam Meningkatkan Cara Membaca Al Qur’an Santri di TPQ Baitul Ilmi Kencong - M. Ainun Naja; Nanang Budianto (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study is motivated by the need to improve the quality of Qur'anic reading instruction in Islamic education institutions, particularly through the implementation of the Tartili method, which is considered systematic and effective. The aim of this research is to examine the implementation of the Tartili method in teaching Qur’anic reading and to evaluate its effectiveness in improving students’ reading abilities at TPQ Baitul Ilmi Kencong. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The informants include teachers, students of various age groups including elderly learners and student guardians. The findings reveal that the Tartili method is applied gradually through a structured "jilid" (book-level) system and is effective in enhancing pronunciation, tajweed comprehension, and fluency. Moreover, the method positively impacts affective aspects such as students’ confidence and learning motivation. Nevertheless, its effectiveness is still constrained by inconsistent attendance, limited parental involvement, and the absence of standardized written assessments. This study recommends continuous teacher training, improvement of instructional management, and strengthened collaboration between teachers and parents to support the sustainability and quality of the Tartili method in TPQ institutions more broadly.